Digital Deception: The Impact of Deepfakes on Privacy Rights (Lex Scientia Law Review, 2024)
Deepfake technology, which uses advanced artificial intelligence to create synthetic media, poses significant threats to privacy rights. Since its emergence, deepfakes have been used in various malicious ways, raising urgent concerns about their impact on privacy rights. This study investigates the implications of deepfake technology on privacy, with a focus on how it affects individuals and legal frameworks. The research is driven by the need to understand the extent of privacy violations and the adequacy of current laws in addressing these challenges. The article aims to provide a comprehensive analysis of the intersection between deepfake technology and privacy rights. It explores the theoretical implications of deepfakes on privacy, assesses public awareness and concern through empirical research, and evaluates existing legal frameworks in the United States, European Union, and India. A mixed-method approach is used in this article. Doctrinal research involves examining profound impact of deepfake technology on privacy rights and analysing legal frameworks and case law to understand the legal responses to deepfakes. Empirical research includes a survey conducted with diverse respondents in India to gauge public awareness, experiences, and opinions regarding deepfakes and its incursion into privacy rights. The study finds that while some jurisdictions have enacted laws to combat deepfakes, significant gaps remain in protecting privacy rights. Empirical findings reveal varying levels of public awareness and concern, highlighting the need for more robust legal measures and public education. The research underscores the necessity for updated and comprehensive legal frameworks to address the evolving challenges posed by deepfake technology. Recommendations include enhancing legal protections while coming up with technological solutions and increasing public awareness to safeguard privacy in the digital age.